Buy What is Advertised on Television? Evidence from Bans on Child-Directed Food Advertising. (September 2013) - Huang, Rui; Yang, Muzhe
The authors examine whether the Children's Food and Beverage Advertising Initiative (CFBAI), the food industry's self-regulatory program that restricts child-directed advertising, has been effective in reducing children's advertising exposure and in changing household purchasing behaviors. During 2006–2008, Hershey's, Mars, and Cadbury Adams implemented their CFBAI pledges. The current findings indicate that CFBAI implementation reduced purchasing frequency by households with children of Cadbury Adams's bubble gum (by 80%) but not Hershey's or Mars chocolate. This seems to have resulted from Cadbury Adams's eliminating advertising to all age groups, whereas children continued to be exposed at high levels to Hershey's and Mars chocolate advertising on general programs. The authors conclude that restricting (only) child-directed advertising may not effectively reduce advertising exposure to children, but reducing advertising exposure can significantly lessen household purchasing.